Evaluation of several protein a resins for application to multicolumn chromatography for the rapid purification of fed‐batch bioreactors. (26th April 2017) - Hilbold, Nicolas‐Julian; Le Saoût, Xavier; Valery, Eric; Muhr, Laurence; Souquet, Jonathan; Lamproye, Alain; Broly, Hervé
Abstract : Most of the existing production capacity is based on fed‐batch bioreactors. Thanks to the development of more efficient cell lines and the development of high‐performance culture media, cell productivity dramatically increased. In a manufacturing perspective, it is necessary to clear as quickly as possible the protein A capture step to respect the manufacturing agenda. This article describes the methodology applied for the design of a multicolumn chromatography process with the objective of purifying as quickly as possible 1, 000 and 15, 000 L fed‐batch bioreactors. Several recent and reference protein A resins are compared based on characteristic values obtained from breakthrough curves. The importance and relevance of resin parameters are explained, and purposely simple indicators are proposed to quickly evaluate the potential of each candidate. Based on simulation data, the optimum BioSC systems associated with each resin are then compared. The quality of the elution delivered by each resin is also compared to complete the assessment. © 2017 American Institute of Chemical Engineers Biotechnol. Prog., 33:941–953, 2017